A NUMERICAL INVESTIGATION OF NANOFLUIDS FORCED CONVECTION FLOW IN A HORIZONTAL SMOOTH TUBE - Demir, Hakan; Dalkilic, Ahmet Selim; Kurekci, Nuri Alpay; Kelesoglu, Bulent; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2010)
In this study, laminar and turbulent forced convection flows of a nanofluid consisting of water and Al2O3 in a horizontal smooth tube with constant wall temperature are investigated numerically. Studies that are related to the subject in the literature are reviewed. The determination of the nanofluid properties is calculated by means of the correlations of Palm et al. Two-dimensional elliptical governing equations are used to study the hydrodynamics and thermal behaviors of the nanofluid flow. A single-phase model is employed with either constant or temperature dependent properties. The investigation is performed for a constant particle size. The velocity and temperature vectors are presented in the entrance and fully developed region. Effects of nanoparticles concentration and Reynolds number on shear stress and pressure drop are presented. The Nusselt numbers and heat transfer coefficients of nanofluids are obtained for different nanoparticle concentrations. Numerical results show the heat transfer enhancement due to presence of the nanoparticles in the fluid. Heat transfer coefficient increases with increasing the particle volume concentration and also increasing wall shear stress values.
Keywords: HEAT-TRANSFER ENHANCEMENT; THERMAL-CONDUCTIVITY; FLUIDS; Thermodynamics; Engineering; Science & Technology - Other Topics; Materials Science